A global database of nitrogen and phosphorus excretion rates of aquatic animals. Issue 5 (18th April 2017) - Vanni, Michael J.; McIntyre, Peter B.; Allen, Dennis; Arnott, Diane L.; Benstead, Jonathan P.; Berg, David J.; Brabrand, Åge; Brosse, Sébastien; Bukaveckas, Paul A.; Caliman, Adriano; Capps, Krista A.; Carneiro, Luciana S.; et al.
Abstract: Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology (MTE) and ecological stoichiometry (ES). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10, 534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES, as described in Vanni and McIntyre (2016; Ecology DOI:10.1002/ecy.1582 ).